PENGARUH JUMLAH DAN SUDUT KEMIRINGAN TERHADAP KECEPATAN PUTARAN BALING-BALING DAN TINGKAT KEBISINGAN YANG DIHASILKAN KIPAS ANGIN SEDERHANA - Thea Deninta; Wahyu Syahputra; Yuniati Yuniati; Dona Mustika (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
The study aims to determine the effect of the number of blades and the angle of inclination on rotation speed on a simple fan and to find out the effect of the number of blades and the angle of inclination to the noise produced by a simple fan. The research method was carried out by the experimental method using a simple fan design. The results of this study, namely the angle of the propeller angles greatly affect the value of the rotation speed of a simple fan blades, the rotation speed at an angle of 0° to the number of blades obtained the highest value, namely the propeller (2) with the measurement results, namely 9559 rpm; measurement of rotation speed at an angle of 15° to the number of blades obtained the highest value, namely the propeller (3) with the measurement results, which is 14353 rpm; measurement of rotation speed at an angle of 30° to the number of blades obtained the highest value, namely the propeller (3) with the measurement results, namely 4473.67 rpm. The number of blades and the angle of the slope affects the noise level produced by a simple fan the lowest noise level at angle 0° to the number of blades (4) with the measurement results, which is 57.4 dB; the lowest noise level at an angle of 15° to the number of blades (3) with the measurement results, which is 65.6 dB; the lowest noise level at an angle of 30° to the number of blades (4) with the measurement results, which is 60.5 dB. The highest rotation speed of the three propellers (2, 3, 4) with angular tilt (0°, 15°, 30°) is the number of propellers (3) at 15° angle tilt with the measurement results, which is 14353 rpm. The lowest noise level is produced from the three propellers (2, 3, 4) with the angle slope (0°, 15°, 30°) is the number of propellers (4) at the angle of 0° with the measurement results, which is 57.4 dB.